A new species of Xenasmatella (Polyporales, Basidiomycota) from southern China - Liu, Zhan-Bo; Yuan, Yuan (Phytotaxa, 2022)
A new species of Xenasmatella, based on morphology, and molecular analysis (using the nuc rDNA ITS1-5.8S-ITS2 (ITS) dataset), was found growing on the underside of rotten bamboo in Yunnan Province, China. X. roseobubalina is characterized by annual, resupinate basidioma with a pinkish buff hymenophore, a monomitic hyphal system, thin-walled generative hyphae with clamp connections, abundant crystalline matter among the hyphae, the absence of cystidia and cystidioles, and broadly ellipsoid to subglobose basidiospores measuring 3.8–5 × 3.3–4 μm. We present the new species with illustrated description and comparisons to closest species as well as a key to the species of Xenasmatella known from China.